Effect of Employment Conflict and Work Stress on Employee Performance of PT. Sulselrabar - Muhammad Yusuf; Hasriani Darlis (Universitas Muhammadiyah Makassar, 2022)
This study aims to find out the Effect of Work Conflict and Work Stress on the Performance of Pt. Office Employees. PLN (persero) The Parent Unit of Sulselbar Region. The data collection technique used in this study is the data collection method used in this study is to use questionnaires. The sample used in this was as many as 70 respondents. The data analysis technique used is multiple linear regression analysis that is processed using the help of SPSS 26 Software. The results shower that the work conflick variable had a significant effeck on employee performance where the significance value was 0.048 0.05. Likewise, work stress has a significant effect on employee performance where the significance value is 0.007 0.05. And simultaneously work conflict and work stress have a significant effeck on employee performance with a significance value of 0.000 0.05 with a coefficient of determination of 32.6%. This explains the percentage of the influence of work conflick and work stress on employee performance by 32.6% while the remaining 64.7% is influenced by other variables